Old Lithuanian plęšti - Smoczyński, Wojciech (Vilnius University Open Series, 2021)
Old Lithuanian plęšti ‘rejoice, jump in joy, dance’ may be interpreted as a back-formation from *plenšoti, a verb borrowed from Old Polish plęsać.